Inovação tecnocientífica no Brasil: uma análise do contexto normativo e conceitual da inovação e a (in)definição dos seus limites éticos - Willig, Júnior Roberto (Universidade do Vale do Rio dos Sinos, 2014)
The protection and promotion of human being in the technoscientific innovation process is the focus of this research. Through ethical responsability, represented by the limits of the protection and promotion of human being, it is intended to verify and identify the legal system and the ethical limits os human behavior before Humanity. In contemporary society, called technoscientific society, that values especially the economics of innovation, in which it reaches ad advanced stage of the technique, near what was considered divine powers, locate the ethical boundaries of technoscience is fundamental and essential to maintenance of life on our planet. In this context and focusing on the actual process of innovation in Brazil, the study is aimed to determine the concept and legal framework for innovation in Brazil, warn about the risks and necessary ethical boundaries of innovation and identify the conceptual and normative context of technoscientific innovation in Brazil, characteristics that demonstrate concern for ethical standars for the promotion and protection of the human being in contemporary society. In the present scenario, the marginalization of the human being, a being traditionally vulnerable, in relation to progress and risk of technoscience is unacceptable, whether at the national or internacional level. Let the human being at the mercy of economic objectives, corporate or institutional interests or discussions of power, minimizing fundamental rights of the human person, brings scenes of inequality and economic, social and environmental risks. Therefore, the importance of this research that seeks to identify a concern or not with the ethical elements embodied by the insertion of human and environmental convervation in the Brazilian innovation scenario.
Keywords: Inovação tecnocientífica; Ética; Sociedade; Ser humano; Lei da Inovação; Lei do bem; Techoscientific innovation; Ethics; Society; HUman Being; Innovation Act; Well Act; ACCNPQ::Ciências Sociais Aplicadas::Direito